Associations between parent perceived social cognitive factors and child objectively measured physical activity behaviors among preschool-aged children. (July 2022) - He, Qing; Ha, Amy S.C.; Ng, Johan Y.Y.; Cairney, John; Bedard, Chloe
Abstract: Grounded in social cognitive theory (SCT), this study sought to examine whether parents perceived social cognitive factors regarding children's physical activity (PA) behaviors were associated with preschool children's moderate-to-vigorous PA (MVPA) levels. A total of 142 Hong Kong parent-child pairs from five preschools/childcare centers completed all assessments in the cross-sectional study. Children's (42% girls; mean age = 4.52 ± 0.67 years) PA was measured through accelerometers. Parents (74% mothers; mean age = 37.38 ± 4.63 years) completed a paper-based questionnaire assessing the social cognitive factors on their children's PA participation. The data were analyzed using latent variable structural equation modeling. Findings revealed that the model showed acceptable fit with the data: χ 2 (23) = 38.14, p  = .025, χ 2 /df = 1.66, CFI = 0.955, TLI = 0.929, RMSEA = 0.068, 90% CI [0.025, 0.106], and SRMR = 0.072. The model accounted for 39.1% of the variance in the PA behavior of preschool-aged children. Structural equation modelling revealed parental self-efficacy (β = 0.29, 95% CI [0.95, 0.49]) and goal setting (β = 0.25, 95% CI [0.06, 0.44]) were directly associated with children's MVPA. Outcome expectations (β = 0.09, 95% CI [0.01, 0.03]) and goal setting (β = 0.18, 95% CI [0.05, 0.32]) mediated the association between parental self-efficacy and children's MVPA. Indirect associations of parental self-efficacy from setting goals via parental support (β = 0.15, 95%CI [0.02, 0.30]) and perceived barriers (β = 0.15, 95% CI [0.05, 0.28]) were uncovered. Results supported the use of SCT in understanding how the parents perceived social cognitive factors predict the PA behaviors of young children. This study provides insight into whether these theoretical variables could be modified or promoted in future intervention programs. Enhancing parents' abilities to ensure preschool-aged children are physically active is of great importance given the global decline in PA among children. Highlights: Social cognitive theory represents a useful model to understand preschool-aged children's physical activity. Parental self-efficacy and goal setting exerted a direct effect on children's physical activity levels. Goal setting was found to mediate the relationship between parental self-efficacy and child moderate-to-vigorous physical activity. Parents play a pivotal role in shaping and sustaining their children's physical activity behaviors.